A Model of Collaborative Governance for Community-based Trophy-Hunting Programs in Developing Countries - Ullah, Inayat; Kim, Dong Young (Perspectives in Ecology and Conservation, 2020)
This paper adopts the Ansel & Gash (2008) model of collaborative governance to frame the structure of community-based trophy hunting (CBTH) programs as a form of collaborative governance that involves multiple stakeholders in the management of common pool resources. We conduct a meta-synthesis of 80 published studies on community-based conservation (CBC) and CBTH programs and develop contingency propositions that may help practitioners and governments to understand and implement programs that seek environmental conservation in collaboration with local communities. Regarding the initial conditions to engender CBTH in developing countries, we propose that the failure of conventional top-down conservation policies, perception of local communities about potential benefits from CBTH, and existence of facilitative leadership, such as local or international conservation NGOs will play critical roles in initiating CBTH, even under the prehistory of conflict, power imbalance, and lack of trust. We also propose organic and instrumental leadership from community and government and inclusive design that creates ground rules and basic protocols are important outside factors to induce stable and strong commitment from participants during the collaboration process. Inside collaborative process, constructive, trust-building face-to-face meetings and generation of intermediate outcomes are identified as crucial factors to building a momentum for successful CBTH outcomes.